Project Based Learning Using Power System Training Device - Goro Fujita; Arwindra Rizqiawan (Jurnal Pendidikan Sains, 2017)
Abstract: For an electrical engineer, training of power system configuration and operation is an essential problem. This paper proposes new training device which consists of separated circuit blocks (module). For example, induction generator, inverter, capacitor, measurement, are used. The trainee selects and assembles them to build a circuit then easy to conduct an experiment. This methodology is effective for group work so as it may be used for PBL (Project Based Learning) program. The concept and required skill to build this device are introduced in this paper.Key Words: training device, PBLAbstrak: Bagi insinyur kelistrikan, pelatihan tentang konfigurasi sistem tenaga dan operasi adalah penting. Tulisan ini mengusulkan perangkat pelatihan baru yang terdiri dari blok rangkaian terpisah (modul). Sebagai contoh, dalam modul ini digunakan generator induksi, inverter, kapasitor, pengukuran. Trainee memilih dan merakit untuk membangun sebuah sirkuit yang mudah untuk digunakan sebagai percobaan. Metodologi ini efektif digunakan untuk kerja kelompok sehingga dapat digunakan untuk PBL (Project Based Learning) Program. Konsep dan keterampilan yang diperlukan untuk membangun perangkat ini, diperkenalkan dalam makalah ini.Kata kunci: perangkat pelatihan, PBL